ANTI DIABETIC ACTIVITY BY THE IN VITRO ALPHA AMYLASE AND ALPHA-GLUCOSIDASE INHIBITORY ACTIVITY OF CATHARANTHUS ROSEUS - V. MALATHI; S. SATHANA DEVI; D K. REVATHI (The Bioscan, 2010)
Catharanthus roseus is a plant extensively known for its anti-inflammatory potential. In this study the alcoholic extract of flower and leaf of Catharanthus roseus was tested for its α-amylase and α-glucosidase inhibitory activity to understand its anti-diabetic potential.Varying concentration of the extracts of leaf and flower were assayed for their inhibitory action [in vitro] on serum amylase, pancreatic amylase, α–amylase from fermented barley and α- glucosidase. Both extracts of the leaf and flower were found to inhibit the enzymes considerably. The leaf extract showed maximum inhibitory action with a concentration of 10 mg/mL [IC50]. IC50 for the flower extract was found to be at a concentration of 12.5mg/mL. Further the anti-oxidant property of the herb was also evaluated by its activity to inhibit lipid per oxidation. Catharanthus roseus extract of leaf and flower exhibit their anti-diabetic effect by inhibiting the enzymes which has a main role in carbohydrate metabolism like α-amylase and α-glucosidase.